In vitro study of momordin Ic in improving atopic dermatitis by regulating claudin-1/MyD88 and targeting NLRP3 - Ying Guo; Litao Wang; Jing Zhang; Tingting Jing; Lefan Fu; Guoying Miao (Polskie Towarzystwo Farmaceutyczne, 2024)
Atopic dermatitis (AD) is a non-infectious inflammatory skin disease characterized by persistent itching of the skin, and it has become a global health problem with increasing incidence and complex pathogenesis. Momordin Ic (MMI) is a triterpenoid saponin that has anti-inflammatory effect and may play an effective role in the treatment of AD. To explore the molecular mechanism of MMI in relieving AD, and to provide some experimental data for the clinical application of MMI in AD. The mRNA levels of IL-33, IL-4 and NF-κB were detected by RT-qPCR. The protein expressions of Filaggrin, Claudin-1, MyD88 and NLRP3 were detected by western blotting. Transepithelial/transendothelial electrical resistance (TEER) method was used to detect the tight-junction function of HaCaT cells. Molecular docking experiment was performed on CB-DOCK2 to predict the binding of MMI and NLRP3. MMI reversed the decrease of filaggrin protein expression and intercellular resistance in HaCaT cells induced by TNF-α and IFN-γ. In addition, MMI reversed the increase in IL-33 and IL-4 mRNA levels in HaCaT cells treated with TNF-α and IFN-γ. In addition, MMI promoted the expression of Claudin-1 and inhibited the expression of MyD88 and NLRP3. In addition, the molecular docking results showed that MMI and NLRP3 had interaction sites. MMI improved the inflammatory response of HaCaT cells by regulating the expression of Claudin-1/MyD88 and targeting NLRP3, which may act a positive role in relieving AD.